Ambiguous Pakistani-Muslim masculinities in the diaspora: a study of Nadeem Aslam's Maps for Lost Lovers. Issue 2 (3rd July 2017) - Mirza, Maryam
ABSTRACT: Nadeem Aslam's Maps for Lost Lovers (2004) is expressly concerned with questions of gender inequality, gendered violence and religious orthodoxy within a diasporic Pakistani-Muslim community in England, which is shown to contrast sharply with the freedoms offered by the 'modern' host society. In examining and denouncing the brutalities against women within the community, the novel grapples with multiple manifestations of masculinity, both oppressive and oppressed. As this article demonstrates, the ambiguous portrayal in the text of British-Muslim masculinities complicates the Islam–West and orthodoxy–modernity binaries that the narrative constructs in order to condemn various forms of brutality against women, and by extension also problematises the feminist project of the novel which rests on these oppositional dichotomies.